Deep vein thrombosis in donor or recipient veins encountered during lower extremity reconstruction with a free anterolateral thigh perforator flap: How do we deal with it? - Jeong, Seong-Ho; Namgoong, Sik; Dhong, Eun-Sang; Han, Seung-Kyu (Frontiers in Surgery, 2022)
Background: The free anterolateral thigh perforator (ALTP) flap has been successfully adopted to reconstruct traumatic soft tissue defects in the lower extremities. However, the occurrence of deep vein thrombosis (DVT) in donor or recipient veins has been overlooked, and there has been no reliable guideline to manage it. Therefore, in this study, we review our cases where the ALTP flaps were transferred to traumatic lower limbs even though DVT was found in the pedicle or recipient veins. Furthermore, based on our experiences, we suggest an algorithmic approach for dealing with DVT. Patients and Methods: This study included 108 patients who underwent lower extremity reconstruction using a free ALTP flap between January 2014 and January 2021. All medical records were reviewed, including preoperative assessment data, intraoperative findings, and postoperative complications. Notably, when DVT was found in both the donor and recipient veins, we thoroughly assessed operative findings, surgical solutions, and final outcomes. Results: Sixty-one of 108 (56.4%) patients underwent computed tomographic venography (CTV) preoperatively, revealing DVT in 11 of these 61 (18%) patients. Three of these 11 patients had iliofemoral DVT, and surgery was delayed more than two weeks after detection. The remaining eight patients had calf DVT and underwent free ALTP flap transfer as scheduled. Conversely, 47 of 108 (43.6%) patients did not undergo CTV, and an occult DVT was found in five of these 47 (10.6%) patients. In two of these five patients, free flap surgery was replaced with amputation and local flap coverage. In the remaining three patients and one patient with an occult DVT that was not found on CTV, the free ALTP flap transfer was carried out. In 15 patients with DVT, free ALTP flap transfer was performed using various alternative methods for venorrhaphy. Consequently, all flaps survived, with partial necrosis occurring in two patients. Conclusion: If DVT-affected veins are appropriately managed, the free ALTP flap can be successfully transferred to the traumatic lower limb even when DVT occurs in donor or recipient veins. Using the author’s algorithm, surgeons can overcome the insufficiency of veins for pedicle anastomosis and obtain optimal reconstructive outcomes.